Pengaruh Sport Education Model Terhadap Motivasi Belajar Siswa Di Smp Nu Darul Ma’arif - Fikri Zulfikar; Agi Ginanjar; Riki Ramadhan (PT. Hasba Edukasi Mandiri, 2025)
This study aims to determine the effect of the Sport Education Model on students' learning motivation at SMP NU Darul Ma’arif Kaplongan. The research design used is a True Experimental Design with a Posttest-Only Control Group Design approach. The sample was selected using a random sampling technique, involving 8th-grade students in the 2019–2020 academic year. In this study, two classes were randomly selected, with one class assigned as the experimental group and the other as the control group. The experimental group received treatment using the Sport Education Model teaching method, while the control group did not receive any specific treatment. The research instrument was a questionnaire used to measure students’ learning motivation. The results showed that students in the control class had lower learning motivation, which was attributed to a lack of interest in the sports being taught and limited basic sports skills. In contrast, students in the experimental class who were taught using the Sport Education Model showed a significant increase in learning motivation. This model allowed students to participate according to their abilities and interests, which ultimately enhanced their enthusiasm and motivation in learning. These findings confirm that the Sport Education Model can be an effective strategy to improve students' learning motivation in physical education through a more personalized and interest-based approach.